A study on top management commitment towards quality management and ISO 9001 certification in the context of Malaysian construction organizations - Tan, Chin Keng (2014)
Malaysian government strongly encourages the Malaysian construction organizations to obtain ISO 9001 certification. It is to produce construction organizations practising standards those are recognized not only in Malaysia but also abroad. Among the efforts taken is the proposal that G7 class construction organizations be required to obtain ISO 9001 certification if they want to vie for government and foreign contracts. Based on literature reviews, many researchers claimed that top management commitment towards quality management is an important factor in quality management. In relation to this, the issue here is whether there is difference between ISO 9001 certified construction organizations and non ISO 9001 certified construction organizations in terms of top management commitment towards quality management in the context of construction industry of Malaysia. This research aims to determine the level of top management commitment towards quality management and whether there is difference on top management commitment towards quality management implementation between construction organizations with and without ISO 9001 certification. The research methodology of questionnaire survey is applied in data collection for the research. 134 responses were received from the questionnaire survey. The data were analysed with descriptive statistics. The research findings indicate that the top management of construction organizations are committed towards quality management on the aspects of quality goals, efforts, involvement, attitude to change and resource allocation. Nevertheless, evidences reveal that quality has not been perceived as a priority if compared with time and cost. As regard to the differences between construction organizations with ISO and without ISO certification towards quality management, those organizations with ISO certification are found putting higher priority to quality, putting more efforts for quality management and having more positive attitude towards changes for the purpose of quality management if compared with organizations without ISO certification.